Word Formation Analysis of English Slang Language on Furious 7 Movie - Delvary, Alvin; Rosita, Nur (English Language and Literature, 2023)
This study is an analysis of slang words found in the dialogues of the Furious 7 movie. This study aims to determine the types of word formation and the function of the slang words used in the Furious 7 movie. The theory used in this research is Yule (2010) regarding the types of word formation and Allan & Burridge's (2006) about the function of slang. This research is a descriptive research with a qualitative approach to solving research problems. The data used is taken from dialogues between characters in the Furious 7 movie. Researcher found 37 slang words used by the characters in the movie. This study reveals that there are seven types of word formation and seven different functions in the use of slang words The most dominant types of word formation are borrowing and multiple processes with 8 data each, while the most dominant slang function is to initiate relax conversation with 10 data.